+0  
 
0
125
1
avatar

(2x-3)^2

Guest Oct 6, 2017
Sort: 

1+0 Answers

 #1
avatar
+1

Expand the following:
(2 x - 3)^2

(2 x - 3) (2 x - 3) = (2 x) (2 x) + (2 x) (-3) + (-3) (2 x) + (-3) (-3):
2 2 x x - 3 2 x - 3 2 x - 3 (-3)

2 x×2 x = 2×2 x^2:
2×2 x^2 - 3 2 x - 3 2 x - 3 (-3)

2×2 = 4:
4 x^2 - 3 2 x - 3 2 x - 3 (-3)

-3×2 = -6:
4 x^2 - 3 2 x + -6 x - 3 (-3)

-3×2 = -6:
4 x^2 + -6 x - 6 x - 3 (-3)

-3 (-3) = 9:
4 x^2 - 6 x - 6 x + 9

-6 x - 6 x = -12 x:
4x^2 - 12x + 9

Guest Oct 6, 2017

32 Online Users

avatar
avatar
New Privacy Policy (May 2018)
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  Privacy Policy